Abstracts from other journals - Paddy (Paediatric Dentistry, 2005)
Emdogain has been shown in clinical and experimental studies to promote regeneration of all periodontal tissues: cementum with anchoring fibres, a functional, periodontal ligament and alveolar bone in connection with treatment of marginal periodontitis.